Metabolic Signatures Differentiate Rett Syndrome From Unaffected Siblings - Neul, Jeffrey L.; Skinner, Steven A.; Annese, Fran; Lane, Jane; Heydemann, Peter; Jones, Mary; Kaufmann, Walter E.; Glaze, Daniel G.; Percy, Alan K. (Frontiers in Integrative Neuroscience, 2020)
Rett syndrome (RTT, OMIM 312750), a severe neurodevelopmental disorder characterized by regression with loss of spoken language and hand skills, development of characteristic hand stereotypies, and gait dysfunction, is primarily caused by de novo mutations in the X-linked gene Methyl-CpG-binding protein 2 (MECP2). Currently, treatment options are limited to symptomatic management; however, reversal of disease phenotype is possible in mouse models by restoration of normal MECP2 gene expression. A significant challenge is the lack of biomarkers of disease state, disease severity, or treatment response. Using a non-targeted metabolomic approach we evaluated metabolite profiles in plasma from thirty-four people with RTT compared to thirty-seven unaffected age- and gender-matched siblings. We identified sixty-six significantly altered metabolites that cluster broadly into amino acid, nitrogen handling, and exogenous substance pathways. RTT disease metabolite and metabolic pathways abnormalities point to evidence of oxidative stress, mitochondrial dysfunction, and alterations in gut microbiota. These observed changes provide insight into underlying pathological mechanisms and the foundation for biomarker discovery of disease severity biomarkers.